2000
DOI: 10.1021/ic000328t
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Oxorhenium(V) Complexes with 2,2‘-Biimidazole:  The Strong Affinity of Coordinated Biimidazole for Chloride Ions via N−H···Cl- Hydrogen Bonding

Abstract: N,N'-Dimethylbiimidazole and bipyridine (N-N) react with ReOCl3(OPPh3)(Me2S) to give mer-ReOCl3(N-N) compounds. Nonmethylated biimidazole forms a trans-O,O [ReOCl2(OPPh3)(biimH2)]+ cation, which is tightly associated with the Cl- counterion via N-H...Cl- hydrogen bonding. Hydrolysis of ReOCl3(biimMe2) in wet acetone (5% water) leads to the linear oxo-bridged dinuclear species [(OReCl2(biimMe2)2(mu-O)] containing chelated biimMe2. Acetone solutions containing only 1% water yield the bent oxo-bridged dinuclear s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
45
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(53 citation statements)
references
References 53 publications
8
45
0
Order By: Relevance
“…4). The affinity of IM for Cl -via N-H···Cl -hydrogen bond formation as computed in this work is therefore comparable with the GC-Watson-Crick base pairing energy [1] and help estimating the formation energy for the adduct between Re(V)-bisimidazole complexes and Cl - [49]. The value of this latter can be taken as ca.…”
Section: Imidazole···x -(X: CL F) Systemsmentioning
confidence: 56%
See 1 more Smart Citation
“…4). The affinity of IM for Cl -via N-H···Cl -hydrogen bond formation as computed in this work is therefore comparable with the GC-Watson-Crick base pairing energy [1] and help estimating the formation energy for the adduct between Re(V)-bisimidazole complexes and Cl - [49]. The value of this latter can be taken as ca.…”
Section: Imidazole···x -(X: CL F) Systemsmentioning
confidence: 56%
“…As a first example, Re-BIMH 2 (BIMH 2 = bisimidazole) complexes and Cl - [49] form very stable aggregates of the type [ReOCl 3 (BIMH 2 ···Cl)] -both at the solid state and in solution. The observed N···Cl bond distance 3.090(5) Å (average) is in excellent agreement with the value computed at B3LYP or MP2 level of theory in this work (3.095 and 3.050 Å, respectively, see Table 7).…”
Section: 122mentioning
confidence: 99%
“…[15] Recently, Beauchamp et al have shown that some bimH 2 Re III complexes form hydrogen bonds with halides or benzoate anions resulting in ion pairs that are stable in organic solvents. [16,27,28] In an initial work we have shown that NϪH groups of bbimH 2 Ru complexes bind water molecules resulting in hydrogen bonded networks. The variation of the noncoordinating anion determined the supramolecular aggregation in these compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Of the complexes listed in Table 1, [ReOCl 3 (bpy)] [19,21] and [ReOCl 3 (phen)] [22] have been reported before. The analytical [23] and coordination [24,25] chemistry of ppyt complexes has been well-documented, but the only reported rhenium complex is [Re(CO) 3 Cl(ppyt)], [26] which has recently been structurally characterised in this laboratory.…”
Section: O Familymentioning
confidence: 99%